Glomerular disease in chronic graft versus host disease - Leticia Peluffo; Lucía Barceló; Gabriela Otatti; Andrés Urrestarazu; Ruben Coitiño; Cecilia Baccino; Sofía San Román; Agustín Noboa; Jimena Cabrera; Haydee Aunchaunya; Fernanda Varela; Cecilia Coelho; et al. (Nefrología (English Edition))
Allogeneic hematopoietic progenitor cell transplantation is a widely used procedure, and graft-versus-host disease (GVHD) is a common complication. Glomerular involvement due to GVHD is exceptional. Objective: to describe the clinical and histopathological presentation of patients with glomerular disease secondary to GVHD. Materials and methods: a retrospective review of the Uruguayan registry of glomerulopathies was conducted to identify renal biopsies from patients with confirmed GVHD. Results: seven patients were identified, four male, with a median age of 41 years (range 8–58). The most common clinical and analytical presentation was nephrotic syndrome. Histopathological findings included membranous glomerulonephritis (4), segmental and focal sclerohyalinosis (1), membranoproliferative glomerulonephritis (1), and thrombotic microangiopathy (1). All patients were treated with corticosteroids in combination with immunosuppressors, most frequently mycophenolate mofetil and rituximab. Five patients achieved complete remission, one had partial remission, and one did not respond. The combination of corticosteroids with rituximab showed a good response rate in those presenting with podocytopathy in the renal biopsy. Resumen: El trasplante alogénico de progenitores hematopoyéticos es un procedimiento ampliamente utilizado y el desarrollo de enfermedad injerto versus huésped (EIVH) una complicación frecuente. El compromiso glomerular por EIVH es excepcional. Objetivo: describir la presentación clínica e histopatológica de pacientes con enfermedad glomerular secundaria a EIVH. Material y métodos: se revisó retrospectivamente el registro uruguayo de glomerulopatías en busca de biopsias renales de pacientes con EIVH demostrada. Resultados: se identificaron 7 pacientes, 4 de sexo masculino, edad 41 (8–58) años. La presentación clínica-analítica más frecuente fue el sindrome nefrótico. Los hallazgos histopatológicos fueron glomerulonefritis membranosa (4), esclerohialinosis segmentaria y focal (1), glomerulonefritis membranoproliferativa (1) y microangiopatía trombótica (1). La totalidad de pacientes se trataron con corticosteroides asociados con inmunosupresores, más frecuentemente micofenolato mofetilo y rituximab. Presentaron remisión completa 5 pacientes, remisión parcial 1 y no remisión 1. La combinación de corticoides con rituximab mostró una buena tasa de respuesta en quienes se presentaron con podocitopatía en la biopsia renal.